2019
DOI: 10.1097/md.0000000000015241
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine versus 5-fluorouracil in neoadjuvant chemoradiotherapy of locally advanced rectal cancer

Abstract: Background:The differences in efficacy between capecitabine and 5-fuorouracil (5-FU) in neoadjuvant chemoradiotherapy (CRT) of locally advanced rectal cancer (LARC) are not well recognized. We performed this meta-analysis to analyze the effect of capecitabine and 5-FU on neoadjuvant CRT to more accurately understand the differences between the 2 drugs.Methods:MEDLINE, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and Wanfang Database were performed to identify all published studies investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…There was no signi cant difference in the incidence of other grade 3-4 adverse events between the two groups, suggesting that capecitabine maintenance therapy). The increase in hand-foot skin reaction is similar to the results reported in published meta-analyses by [19], Zhan Wang [6], J. Zhu [20], Z. Wu [21] and others. There was no signi cant difference in the incidence of other grade 3-4 adverse events between the two groups, suggesting that capecitabine maintenance therapy is a safe method.…”
Section: Safety Of Capecitabinesupporting
confidence: 88%
“…There was no signi cant difference in the incidence of other grade 3-4 adverse events between the two groups, suggesting that capecitabine maintenance therapy). The increase in hand-foot skin reaction is similar to the results reported in published meta-analyses by [19], Zhan Wang [6], J. Zhu [20], Z. Wu [21] and others. There was no signi cant difference in the incidence of other grade 3-4 adverse events between the two groups, suggesting that capecitabine maintenance therapy is a safe method.…”
Section: Safety Of Capecitabinesupporting
confidence: 88%
“…In our study, patients who developed early metastases received capecitabine frequently as a radiosensitizer. This does not mean that it is a weaker chemotherapeutic agent but inversely its effect had been approved by multiple studies [ 17 - 19 ]. This result may be attributed to the small number of our patients; hence, further studies with a larger number of cases are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Capecitabine-based neoadjuvant chemoradiotherapy has also shown improvement in pCR, ad R 0 resection, and nodal downstaging in patients with locally advanced rectal cancer when compared with 5-FU-based neoadjuvant chemoradiotherapy. [15] A pharmacoeconomic analysis of capecitabine and 5-FU was carried out by Cassidy et al, [16] wherein clinical effectiveness, chemotherapy costs, expenses toward managing adverse events, and costs for time and travel were assessed. The study showed that the average expenses toward medication for the management of adverse events was lower in the capecitabine treatment arm compared with the 5-FU/LV treatment arm (£86 and £345, respectively) and mean travel cost per patient was lower with capecitabine (£62) compared with 5-FU/LV (£196).…”
Section: Theory Of Oral Versus IV Chemotherapy -The Capecitabine Experiencementioning
confidence: 99%